2021
DOI: 10.1002/adom.202101405
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Laser Switching of Phase‐Change Random Metasurfaces with Tunable ON‐State

Abstract: that differ strongly from those of the constituent materials. Due to this remarkable flexibility, thin-film nanocomposites belong per se to the class of metasurfaces, whose fields of applications are constantly growing in key technological areas, including communications, energy, catalysis, and medicine. In the field of nanophotonics, the use of metasurfaces formed by planar arrangements of metallic and dielectric nanostructures has enabled the control of light at subwavelength scales, allowing light manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In order to characterize the transient optical response of germanium upon ns and fs laser excitation, two different optical probe setups were used: with sub-ns temporal resolution and a temporal window up to several microseconds [20]. The complete temporal evolution of the reflectivity is recorded for a single pulse irradiation at a selected fluence.…”
Section: Experimental Setupsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to characterize the transient optical response of germanium upon ns and fs laser excitation, two different optical probe setups were used: with sub-ns temporal resolution and a temporal window up to several microseconds [20]. The complete temporal evolution of the reflectivity is recorded for a single pulse irradiation at a selected fluence.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…A point-probing real-time reflectivity setup (Figure 1(b)), with sub-ns temporal resolution and a temporal window up to 200 ns [19]. The complete temporal evolution of the reflectivity is recorded for a single pulse irradiation at a selected fluence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in the investigation of bismuth metamaterial, developing lithography-free fabrication methods are highly desired. So far, the bismuth thin film, the bismuth nanoparticles embedded in a dielectric matrix, and the bismuth nanorod array are applied as the optical metamaterials for absorbers [45,[47][48][49][50][51][52], filters [49,53,54], and analog tuners for intensity and phase [55][56][57], as well as for thermaloptical switching [54,58,59]. Additionally, they can be prepared via lithography-free routes including regular physical vapor deposition (PVD) via magnetron sputter or thermal evaporation [32],pulse laser deposition (PLD) [60], and glazing-angle deposition (GLAD) [57].…”
Section: Lithography-free Fabrication Of Bismuth Metamaterialsmentioning
confidence: 99%
“…Bismuth nanostructures are nanoparticles based on the bismuth monoelement used because of its solid–liquid optical contrast with low melting points of about 270 °C. Recently, Alvarez-Algeria et al demonstrated the relevant properties of a random distribution of Bismuth-nanostructures in a dielectric matrix (PCRMs, phase change random metasurfaces). A nanosecond pulsed laser was used to melt the Bismuth-nanostructures with different filling factors, allowing a high optical contrast between the solid and liquid states (on/off state) and fast switching up to 10 ns and semivolatile behavior, which means staying at the melting phase without a permanent power supply for a given time duration.…”
Section: From Current Key Enabling Technologies To Tunable Metasurfacesmentioning
confidence: 99%